Cutting edge: Virus-specific CD8+ T cell clones and the maintenance of replicative function during a persistent viral infection. - Bannard, O; Kraman, M; Fearon, D (2010)
Persistent viral infections induce the differentiation and accumulation of large numbers of senescent CD8(+) T cells, raising the possibility that repetitive stimulation drives clones of T cells to senesce. It is therefore unclear whether T cell responses are maintained by the self-renewal of Ag-experienced peripheral T cell subsets or by the continuous recruitment of newly generated naive T cells during chronic infections. Using a transgenic mouse model that permits the indelible marking of granzyme B-expressing cells, we found that T cells primed during the initial stages of a persistent murine γ-herpes infection persisted and continued to divide during a latent phase of up to 7 mo. Such cells maintained an ability to extensively replicate in response to challenge with influenza virus expressing the same Ag. Therefore, Ag-experienced, virus-specific CD8(+) T cell populations contain a subset that maintains replicative potential, despite long-term, persistent antigenic stimulation.